The Assessment: The Economic Record of the Labour Government Since 1997. - Nickell, S (2002)
In this assessment, we focus on four main areas. First, we consider overall macroeconomic performance, and conclude that the policy changes since 1997 have been a significant success. Second, we consider productivity performance. This has been very modest. We isolate a number of important factors underlying this poor performance, particularly relative to the improving productivity performance of the United States. There have been some key policy changes with regard to competition and R&D; but, given the overall problems, we should not expect any rapid improvement in this area. Third, we look at poverty rates. We discuss the reasons for the dramatic rise in poverty since 1979 and note how the policy changes since 1997 have started to reverse this seemingly inexorable trend. Finally, we set the scene for some of the other studies in this issue by noting the exceptionally low levels of net investment in the public sector since 1975 and the dramatic declines in the relative pay of certain groups of public sector workers since the same date. These trends have strongly exacerbated problems in the key areas of health, education, and transport.